The Effect of Warm Rice Compresses on Breast Engorgement in Postpartum Womens - Dewi Handayani; Ayu Jani Puspitasari (Sean Institute, 2026)
Breast engorgement in postpartum breastfeeding mothers is a common problem frequently encountered. One management strategy that can be applied is a non-pharmacological method using warm rice compresses. This study aims to determine the effect of warm rice compresses on breast engorgement in postpartum breastfeeding mothers. The study design employed a quasi-experimental approach using a pretest-posttest model with a control group. The study sample consisted of 20 breastfeeding postpartum mothers who met the inclusion criteria and were selected using purposive sampling. The measurement tool used was the Six-Point Engorgement Scale (SPES) to assess the level of breast engorgement. The results showed a significant decrease in the level of breast engorgement in the intervention group after the application of warm rice compresses. Statistical analysis yielded a p-value < 0.05, indicating that warm rice compresses have an effect on breast engorgement in postpartum mothers.